2021
DOI: 10.1111/ipd.12776
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to inform the development of a Canadian caries risk assessment tool for use by primary healthcare providers

Abstract: Despite all the advancements in dental prevention over the past decades, the problem of early childhood caries (ECC) still exists. Evidence suggests that whereas the prevalence of caries among older children, youth, and adults has declined, the prevalence of ECC in the preschool population has increased. [1][2][3] For many children with ECC, dental surgery under general anaesthesia is the only treatment option. 4 In-hospital day surgery to treat ECC is the most common day surgical procedure in Canada. 5 A 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 62 publications
(244 reference statements)
0
33
0
Order By: Relevance
“…The successful management of dental caries relies upon assessment of the caries risk of the individual and a treatment plan with personalized therapy that is derived from the details recorded in the risk assessment [13][14][15][16][17][18]. There are numerous published CRA methods and guidelines for caries management several of which are listed in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The successful management of dental caries relies upon assessment of the caries risk of the individual and a treatment plan with personalized therapy that is derived from the details recorded in the risk assessment [13][14][15][16][17][18]. There are numerous published CRA methods and guidelines for caries management several of which are listed in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that the evidence to inform the selection of current CRATs for children is mostly yet to be established. The most recent systematic review by Schroth et al [18] reported extensive assessment of each of the possible caries risk assessment components that contributed to numerous published CRATs. However, the review was done 4 years prior to the paper being published so their extensive tables did not include some of the most recent studies in the field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include diet, oral hygiene, enamel defects, oral microbiota, and saliva buffering capacity and flow rate. 1 , 2 It has been estimated, based on twin studies, that the heritability of dental caries, or the proportion of variation that is due to genes, can reach over 50%. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%